Assessment of Rice Germplasms through DUS Testing Guidelines - Chakravorty, Ashim (Advanced Research in Biological Science Vol. 9, 2024)
A collection of fifty one landraces of rice from gangetic alluvial zone was taken for the evaluation and characterization based on twenty eight essential qualitative traits. Distinctiveness, Uniformity and Stability test (DUS) was done during the kharif season at the research farm of Sripat Singh College, Jiaganj, Murshidabad and at the Zonal Adaptive Research Station, Krishnagar, Nadia, West Bengal. Each cultivar was found distinct in respect to the variability found among the twenty two essential and twenty four additional traits. There was a remarkable variability in respect to anthocyanin coloration in different body parts like seed apicular part, collar, auricle, basal leaf sheath, leaf, seed coat of maximum cultivars. Conservation of these cultivars is now keenly essential for future rice breeding work. These cultivars may serve as a superior germplasm in the coming environmental biotic and abiotic hazards. DUS test is very important tool based on morphological parameters and geographical influence reflecting the genetically background for the particular traits. Mode of exploration of rice cultivars through DUS test would obviously help the rice researchers and scholars to make a promising ground to feed the quality food to the mass saving from hunger.